075 Endothelial function during adolescence predicts left ventricular mass in early adult life. (22nd September 2015) - Lazdam, M; Kylintireas, I; Cunnington, C; Diesch, J; Trevitt, C; Channon, K; Neubauer, S; Singhal, A; Leeson, P
Abstract : Background: Left ventricular mass is a powerful independent predictor of mortality and morbidity in adults. Endothelial function may influence cause cardiac hypertrophy through modification of myocardial biology or arterial stiffness. We sought to determine whether endothelial dysfunction during adolescence and early adult life is independently associated with increased left ventricular mass. Methods: Thirty healthy normotensive subjects (43% males) underwent assessment of endothelial function by flow mediated dilatation (FMD) of the brachial artery at the age of 15 years using ultrasound. Subjects were followed up at the age of 23–26 years for assessment of left ventricular mass (LVM) by cardiovascular magnetic resonance imaging (Siemens 1.5 T Sonata scanner), adjusted for body surface area (LVMI), and repeated FMD measurements using the same methods. Cardiovascular risk factors including body size, blood pressure, lipid profile, glucose tolerance and smoking were assessed at both time points. Results: FMD in early adulthood was significantly related to LVMI (r −0.55, p 0.002). FMD at the age 15 was similarly inversely associated with LVMI 10 years later (r −0.41, p 0.02) with greater endothelial responses related to reduced left ventricular mass. Those with FMD consistently above the mean at both age 15 and 25 had significantly lower LVMI compared to those with FMD below the mean (58 g/m2 vs 68 g/m2 p<0.05). In a multivariate regression model of LVMI, including cardiovascular risk factors, FMD was the main independent predictor of ventricular mass. Conclusion: Endothelial responses during adolescence predict left ventricular mass 10 years later and those with consistently high endothelial responses over this time period have the lowest left ventricular mass. Endothelial function may influence cardiac structure in young people in the absence of classic risk factors such as hypertension and obesity.